Faktor Yang Berhubungan Dengan Pola Konsumsi Fast Food Pada Mahasiswa Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia (Window of Public Health Journal, 2025)
The trend of unhealthy food consumption, such as fast food, raises important concerns regarding changing eating habits. The prevalence of fast food consumption among students may present various health risks. This study seeks to explore the factors influencing fast food consumption patterns among students at the Faculty of Public Health, Universitas Muslim Indonesia, in 2025. Utilizing a quantitative research methodology with a cross-sectional study approach, the study involved a sample of 253 participants drawn from a total population of 692, with an accidental sampling technique employed for participant selection. Data was gathered through a questionnaire, and analysis was conducted using the Chi-Square test. The statistical analysis yielded significant findings: a relationship between knowledge (p = 0.000) and ease of access (p = 0.001) with fast food consumption patterns. In contrast, no significant relationship was identified between parental income and fast food consumption (p = 0.396). In light of these findings, it may be beneficial for the faculty to consider implementing periodic educational campaigns to enhance students' awareness of healthy eating practices. Engaging students through popular media platforms such as Instagram and TikTok could be an effective strategy to promote healthier eating habits.